Serum levels of organochlorine pesticides and polychlorinated biphenyls among inhabitants of Greater Metropolitan Rio de Janeiro, Brazil - Delgado Isabella Fernandes; Barretto Heloisa H.C.; Kussumi Teresa A.; Alleluia Irene Baptista; Baggio Cenira de A.; Paumgartten Francisco José Roma (Cadernos de Saúde Pública, 2002)
Levels of persistent organochlorine pesticides (OCPs) and polychlorinated biphenyls (PCBs) were determined in the blood serum of people living and working in the urban area of greater Rio de Janeiro city. Blood samples from 33 volunteers (16 males, 17 females, 19-63 years old) were taken in January 1999. OCP residues (op'DDT, pp'DDT, pp'DDD, pp'DDE, Aldrin, Dieldrin, Endrin, Heptachlor, Heptachlor-epoxide, alpha-, beta- and gamma-Hexachlorocyclo-hexane, Hexachlorobenzene) and PCBs (congeners: 28, 52, 101, 138, 153, 180) were extracted with n-hexane and analyzed by gas chromatography with electron capture detection. Except for pp'DDE (detection limit = 1.4µg/L) no other OCP residue was found in the samples. No PCB congener (detection limit = 2.0µg/L) was detected either. pp'DDE was found in 17 out of 33 samples in concentrations that ranged from 1.4 to 8.4 µg/L of serum or, on a fat basis, from 0.200 to 3.452 µg/g of serum lipids. Percentage of positive samples (%) and levels of pp'DDE (range of positive samples) increased from the youngest to the oldest group (<=29 yrs: 10%, 0.278µg/g; 30-39 yrs: 60%, 0.200-0.765µg/g; > or = 40 yrs: 77%, 0.257-3.452µg/g).